An Empirical Research on the Ranking of Chinese State-owned Banks in Corporate Social Responsibility - Xin, Huang; Wenzhong, Zhu (Archives of Business Research, 2015)
Purpose - This paper aims to provide a ranking of the four Chinese state-owned banks: Industrial and Commercial Bank of China (ICBC), Bank of China (BC), China Construction Bank (CCB) and Agricultural Bank of China (ABC) based on corporate social responsibility by using an assessment model proposed by Zhu so as to test the model and drive the best CSR performance of these leading Chinese banks. Methodology - The paper ranks the four Chinese state-owned banks by using Zhu’s model (see Sect. Appendix), which covers not only the CSR practice of banks but also management system. Furthermore, our ranking is constructed by content analysis, assigning scores manually. To rank the four banks, we adopted four kinds of information resources: corporate annual report in 2013, CSR annual report in 2013, articles of company and website. Our ranking can be a useful instrument for bank’s self-assessment to find out the existing problems, identify their area to improve in CSR and set proper goal and guidelines to enhance their CSR behavior. Findings - The study finds that the four state-owned Chinese banks are ranked in CSR performance as follows: 1. Industrial and Commercial Bank of China, 2. Bank of China, 3. Construction Bank of China, and 4. Agricultural Bank of China. In general, the four banks can protect stakeholders’ interests and their policies conform to sustainable development and national macroeconomic policies. But improvement is needed for information disclosure, etc. Originality/value - The paper is of great theoretical and practical significance. One the one hand, we fill the gap of lacking empirical research on Chinese bank ranking based on CSR in literature. On the other hand, our research provides clues for a boarder range of banks' ranking based on CSR in the future. For further research, we will apply our model to evaluate all Chinese commercial banks based on CSR and report the ranking annually, providing stakeholders with information about CSR to help them to adjust their decision, and simultaneously providing banks with information about the status quo of their CSR performance and promoting their CSR management.